2014
DOI: 10.1111/ger.12134
|View full text |Cite
|
Sign up to set email alerts
|

Digital panoramic radiographs are useful for diagnosis of osteoporosis in Korean postmenopausal women

Abstract: Thickness and morphological changes of mandibular inferior cortical bone are associated with BMD, independent of age, height and weight. These results suggest that MI, MCI and SVE may be useful indices for the diagnosis of osteoporosis in a Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 33 publications
3
57
2
6
Order By: Relevance
“…It has been reported that the thickness of mandibular cortical bone decreases with age 10 . The mandibular cortical width of Korean women, 60-69 years of age, showed a steep decline 11 . However, we found no significant correlation between mandibular cortical width and age in either men or women, and the presence of osteoporosis did not depend on age.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the thickness of mandibular cortical bone decreases with age 10 . The mandibular cortical width of Korean women, 60-69 years of age, showed a steep decline 11 . However, we found no significant correlation between mandibular cortical width and age in either men or women, and the presence of osteoporosis did not depend on age.…”
Section: Discussionmentioning
confidence: 98%
“…In this study digital panoramic radiographic equipment was used to obtain the images. Digital panoramic technologies have the benefi t of eliminating errors associated with processing and providing the opportunity of using digital enhancement and measuring tools 7,15,16,21,23) . Digital panoramic radiography also limits radiation exposure as it requires a lower dose than conventional panoramic radiography for image formation.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a major public health problem confronting both developed and developing countries. Osteoporosis can affect both children and adults, and is especially detected in postmenopausal women [4][5][6][7] . The typical clinical presentation of osteoporosis is the radiographic detection of bone fractures, largely in the absence of causative trauma.…”
Section: Introductionmentioning
confidence: 99%
“…It is a qualitative analysis, and the endosteal margin is classified as C1, C2 or C3 according to the apparent intracortical bone erosion pattern presented. MCI is supported to be effective in screening patients at low BMD risk, and it is inversely correlated with BMD in many distinct populations [1,7,13] as well as in diabetic patients [7].…”
Section: Onementioning
confidence: 99%
“…O steoporosis is a metabolic disease which affects bone mineral density (BMD) leading to increased low-energy fracture risk [1]. Type 1 and type 2 diabetes are recognized as potential modifier diseases to BMD and osteoporotic fracture risk [2].…”
Section: Introductionmentioning
confidence: 99%